Evaluation of procalcitonin elevation during ICU stay and its relationship with mortality in ICU patients for COVID-19 with respiratory involvement. A multicenter prospective cohort study - Rivera-Fernandez, Ricardo; Yáguez-Mateos, Luis; Guerrero-Marin, María; Pérez-Manrique, Rosa María; Rojas-Amezcua, María; Pontes-Moreno, Antonio Jesús; Ríos-Toro, Juan José; Vela-Colmenero, Rosa; Ruiz-Garcia, María Isabel; Colmenero-Aguilar, Crispín; Castillo-Rivera, Ana; Pola-Gallego de Guzmán, María Dolores; et al. (Frontiers in Medicine, 2022)
Introduction: A multicenter prospective cohort study studied patients admitted to the Intensive Care Unit (ICU) by COVID-19 with respiratory involvement. We observed the number of occasions in which the value of procalcitonin (PCT) was higher than 0.5 ng/ml. Objective: Evaluation of PCT elevation and influence on mortality in patients admitted to the ICU for COVID-19 with respiratory involvement. Measurements and Main Results: We studied 201 patients. On the day of admission, Acute Physiology And Chronic Health Evaluation (APACHE)-II was 13(10-16) points. In-hospital mortality was 36.8%. During ICU stay, 104 patients presented 1 or more episodes of PCT elevation and 60(57.3%) died and 97 patients did not present any episodes of PCT elevation and only 14(14.4%) died(p<0.001). Multivariable analysis showed that mortality was associated with APACHE-II:(OR:1.13(1.03-1.27)), Acute Kidney Injury(OR:2.21(1.1-4.42)) and with the presentation of one or more episodes of escalating PCT:(OR:5.07(2.44-10.53)). Of 71 patients who died, 59.2% had an elevated PCT value on the last day, and of the 124 patients who survived, only 3.2% had an elevated PCT value on the last day (p<0.001).On the last day of the ICU stay, the Sequential Organ Failure Assessment score (SOFA) of those who died was 9(6-11) and 1(0-2) points in survivors (p<0.001). Of the 42 patients who died and in whom PCT was elevated on the last day, 71.4% were considered to have a mainly non-respiratory cause of death. Conclusions: In patients admitted to the ICU by COVID-19 with respiratory involvement, numerous episodes of PCT elevation are observed, related to mortality. PCT was elevated on the last day in more than half of the patients who died. Serial assessment of procalcitonin in these patients is useful because it alerts to situations of high risk of death. This may be useful in the future to improve the treatment and prognosis of these patients.